CYBERSECURITY EDUCATION FOR YOUNG GENERATIONS: THREATS, RISKS, AND SELF-PROTECTION STRATEGIES IN THE DIGITAL WORLD - Satrya Mahardika; Abdul Saboor; Kautsar Hilmi; M. Heru Prayogo; Wildan Hilmy; H. Apridelson Manurung; Ahmad Zulfikar A (Abdi Jurnal Publikasi, 2026)
The rapid growth of digital technology has increased internet use among young people, especially students who actively use social media, messaging applications, online games, and learning platforms. However, this participation is not always accompanied by adequate cybersecurity literacy. As a result, young users may be exposed to phishing, account takeover, malware, online fraud, personal data leakage, identity misuse, and cyberbullying. This community service activity aimed to introduce practical cybersecurity awareness and self-protection strategies for students and teachers. The activity was conducted at SMA Al Wafi Islamic Boarding School, Depok, on 10 April 2026 from 08.00 to 11.00 WIB, involving approximately 300 participants consisting of senior high school students, grade 9 students, and teachers. The method combined interactive presentation, case-based explanation, simple threat-identification simulation, open discussion, and qualitative evaluation through observation and participant feedback. The materials covered common cyber threats, digital privacy, phishing-link recognition, strong password habits, two-factor authentication, one-time password protection, and responsible social media behavior. The results indicated increased awareness based on participant engagement, questions, and observed ability to restate basic cybersecurity practices. The activity also produced practical learning materials and recommendations for sustainable cybersecurity literacy programs in the school environment.